Zonal flow generation and its nonlinear dynamics in trapped electron mode turbulence of flat density tokamak plasmas. (25th May 2016) - Guo, Z.B.; Hahm, T.S.
Abstract: We investigate zonal flow (ZF) generation in ion temperature gradient driven trapped-electron-mode (ITG-driven TEM) turbulence via modulational instability analysis. We show that the acceleration of a seed ZF is a consequence of the competition of negative radiation pressure (NRP, acting as a driving force) and positive radiation pressure (PRP, acting as a retarding force) of the ITG-driven TEM turbulence. A critical dimensionless ion temperature logarithmic gradient ( R / L T i, c ) normalized to the major radius is obtained by balancing the NRP- and PRP effects. For R L T i < R L T i, c, the NRP effect is dominant and the seed ZF is accelerated. Otherwise, the PRP effect is dominant and the seed ZF is decelerated. In addition, a new nonlinear evolution mechanism of the ZF is also proposed. It is shown that the turbulence energy intensity spectrum gets steepened in k -space due to the ZF shearing, which in turn induces nonlinear growth of the ZF.